Saline Flush Test: Can Bedside Sonography Replace Conventional Radiography for Confirmation of Above‐the‐Diaphragm Central Venous Catheter Placement?. (1st July 2015) - Gekle, Robert; Dubensky, Laurence; Haddad, Stephanie; Bramante, Robert; Cirilli, Angela; Catlin, Tracy; Patel, Gaurav; D'Amore, Jason; Slesinger, Todd L.; Raio, Christopher; Modayil, Veena; Nelson, Mathew
Abstract : Objectives: Resuscitation often requires rapid vascular access via central venous catheters. Chest radiography is the reference standard to confirm central venous catheter placement and exclude complications. However, radiographs are often untimely. The purpose of this study was to determine whether dynamic sonographic visualization of a saline flush in the right side of the heart after central venous catheter placement could serve as a more rapid confirmatory study for above‐the‐diaphragm catheter placement. Methods: A consecutive prospective enrollment study was conducted in the emergency departments of 2 major tertiary care centers. Adult patients of the study investigators who required an above‐the‐diaphragm central venous catheter were enrolled during the study period. Patients had a catheter placed with sonographic guidance. After placement of the catheter, thoracic sonography was performed. The times for visualization of the saline flush in the right ventricle and sonographic exclusion of ipsilateral pneumothorax were recorded. Chest radiography was performed per standard practice. Results: Eighty‐one patients were enrolled; 13 were excluded. The mean catheter confirmation time by sonography was 8.80 minutes (95% confidence interval, 7.46–10.14 minutes). The mean catheter confirmation time by chest radiograph availability for viewing was 45.78 minutes (95% confidence interval, 37.03–54.54 minutes). Mean sonographic confirmation occurred 36.98 minutes sooner than radiography ( P < .001). No discrepancy existed between sonographic and radiographic confirmation. Conclusions: Confirmation of central venous catheter placement by dynamic sonographic visualization of a saline flush with exclusion of pneumothorax is an accurate, safe, and more efficient method than confirmation by chest radiography. It allows the central line to be used immediately, expediting patient care.